Initiating Aha moments when implementing person-centered care in nursing homes: a multi-arm, pre-post intervention - Cornelison, Laci J.; Linda, Hermer; Syme, Maggie L.; Doll, Gayle (My University, 2019)
Comprehensive adoption of culture change via person-centered care (PCC) practices in nursing homes has been slow. Change such as this, requires transformation of organizational culture, frequently generating resistance and slow moving change. This study examined how nursing homes perceive their adoption of PCC practices across seven domains and how these perceptions change in response to an educational intervention embedded in a statewide program, Promoting Excellent Alternatives in Kansas nursing homes (PEAK 2.0). Given perception is an important feature of the change process, it was hypothesized that pre-adopters engaging in PEAK 2.0’s initial Foundation year (level 0) would have lower perceived PCC adoption following a year of education and exposure to PCC, whereas adopters (PEAK 2.0 level 1–5 homes) would have higher perceived PCC adoption following a year of participation in their respective level in the program.
Keywords: Long-term care; Skilled nursing facilities; Culture change; Resident-centered care; Organizational change; Pay-for-performance